2020
DOI: 10.6004/jnccn.2020.7672
|View full text |Cite
|
Sign up to set email alerts
|

The Internet as a Route to Health Information, Support, and Healthcare for Cancer Survivors

Abstract: W ith advances in detection and increasingly sophisticated treatments, twothirds of people who are diagnosed with cancer will become long-term survivors. 1 This means that most cancer survivors will live .5 years after their diagnosis. 1 In fact, it is estimated that there are .16.9 million cancer survivors alive in the United States today, and that number is expected to grow to $22.2 million by 2030 with the growth and aging of our population. 2 The growing number of cancer survivors represents both a success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Further, participants experienced significant improvements in patient and caregiver activation, quality of life, social support and supportive care needs. These findings are promising and timely given the increased need for virtual supportive care interventions as a result of the COVID-19 pandemic [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, participants experienced significant improvements in patient and caregiver activation, quality of life, social support and supportive care needs. These findings are promising and timely given the increased need for virtual supportive care interventions as a result of the COVID-19 pandemic [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Suggestions provided by participants to improve integration and coordination included centralizing information about supportive care services, developing virtual/online/telehealth supportive care programming to minimize the need to travel/commute to the cancer centre to access in-person programming, having dedicated professional patient navigators/coaches, and a “one-stop-shop” to access supportive care. These strategies have already been implemented/tested in various ways at different cancer care institutions [ 20 , 21 , 22 , 23 , 24 ]. For example, centralizing information about supportive care services has been developed using eHealth (i.e., web-based Internet search engines or smartphone applications) [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Healthy People 2030 highlights the desire to increase the use of patient portals, particularly the proportion of persons who use health information technology (HIT) to track health care data or communicate with providers, and the proportion of persons who have access to quality (reliable and easy to use) digital health tools and information [ 12 ]. The Internet is and will continue to be a major source for people to receive health information as it plays an increasingly important role in health care and as individuals become more aware and receptive to new technologies such as the Internet [ 13 ]. Studies have shown that greater participation in the Internet and social media may be related to the improvement of health behaviors and health conditions, indicating the growing important of the Internet in health maintenance [ 14 ].…”
Section: Introductionmentioning
confidence: 99%